Adjunct Constructions in Modern German: Shaping Narrative and Subjectivity in Discourse: Konstruksi Adjektiva dalam Bahasa Jerman Modern: Membentuk Narasi dan Subjektivitas dalam Wacana - Yarkulovna, Namazova Nazira (Academia Open, 2025)
General Background: Modern German syntax is undergoing a transformation, influenced by broader shifts in language use, with an increasing focus on subjectivity and expressiveness in written discourse. Specific Background: Among these changes, adjunct constructions have gained prominence as devices that enhance emotional nuance and communicative depth, reflecting the speaker's intentionality and facilitating pragmatic interaction with the listener or reader. Knowledge Gap: Despite their stylistic and grammatical exploration, the communicative-syntactic functions of adjunct constructions—especially in conveying the author's egocentric viewpoint and pragmatic intentions—remain underexplored. Aims: This study investigates how adjunct constructions in contemporary German function as communicative-syntactic tools, highlighting their role in shaping narrative perspective, affecting meaning, and interacting with both linguistic and extralinguistic factors. Results: The findings reveal that adjunct constructions are multifunctional elements with descriptive, expressive, and evaluative roles, enhancing the emotional and intellectual impact of texts. They support postmodern narrative features like fragmentation and spontaneity. Novelty: This research offers a fresh cognitive-communicative lens on syntax, focusing on the interaction between speaker subjectivity and reader engagement. Implications: The study contributes to linguistic theory, stylistic analysis, and German language pedagogy, advancing the understanding of pragmatics and syntax in literary discourse. Highlights: Adjunct constructions enhance emotional depth and narrative perspective. They convey the author's subjective viewpoint and pragmatics. The study explores syntax-pragmatics interaction in modern German discourse. Keywords: Modern German syntax, adjunct constructions, narrative perspective, pragmatics, emotional nuance.